(untitled) (Journal of Medicine, 2011)
Osteoarthritis (OA) is a leading cause of disability in the elderly. The goal of OA treatment is to control symptoms, prevent disease progression, minimize disability, and improve quality of life. The management can be divided into non pharmacologic interventions, pharmacologic interventions, and surgical options. Pharmacologic interventions can be further subdivided into symptomatic therapy and potential structureor disease-modifying therapy. There are, at present, no specific pharmacologic therapies that can prevent the progression of joint damage due to OA. Acetaminophen is the first line of therapy, although most of the patient requires NSAIDs. Risk of gastrointestinal (GI) bleeding and cardiovascular risk need to be considered, especially for elderly. With inflammatory components, intra-articular glucocorticoid injection gives short term benefit. Compared with corticosteroid injections, hyaluronan injections have similar clinical effects. But it is more costly. So far research with potential structure- and disease-modifying drugs in osteoarthritis includes tetracyclines, glycosaminoglycan polysulfuric acid, pentosan polysulfate, diacerein, glucosamine and others. Scientists are looking for new therapeutic targets like IL-1 receptor antagonist (IL-1Ra), mitogen-activated protein (MAP) kinases inhibitors, NF-kappaB inhibitors. Gene therapy, Chondrocyte and stem cell transplants showed some promise in animal models. Keyword: Osteoarthritis, pharmacologic therapy, disease modifying therapy DOI: http://dx.doi.org/10.3329/jom.v12i2.7690 JOM 2011; 12(2): 142-148